Catasetum tavaresii (Catasetinae), a new species from Central Brazilian Amazon - Passos Krahl, Dayse Raiane; Sena de Oliveira, Miguel; Schmal, Philippe; Chiron, Guy; Batista Fernandes da Silva, João; Krahl, Amauri Herbert; Moreira da Silva de Almeida, Sheylla Susan; de Castro Cantuária, Patrick (Lankesteriana: International Journal on Orchidology, 2023)
A new Catasetum species from Brazilian Amazon, more specifically from the “Floresta Nacional de Saracá-Taquera” (State of Pará), is proposed, described and illustrated. This new taxon belongs to the subgenus Catasetum, section Isoceras, subsection Isoceras, whose representatives have symmetrical and parallel antennae. It is compared with C. nhamundaense, C. garnettianum and C. barbatum, all with the same antennae characteristics and belonging to the "C. cristatum alliance". Among related species, C. tavaresii differs mainly in the lip structure. We also give data on geographical distribution, habitat, phenology, flower visitors, and preliminary conservation status.